Resonance of total rejection produced by a thin vertical stepped conductor in rectangular waveguide - Kirilenko, A. A.; Prikolotin, S. A. (Видавництво Національного університету "Львівська політехніка", 2009)
The problem of the dominant ТЕ10 mode diffraction by a thin step bended metallic bar placed in a rectangular waveguide (fig. 1) is considered. Placing such a bar into rectangular waveguide cross-section affects on the appearance of the TE10 mode total reflection resonance in the single mode frequency band. Influence of the bar geometrical dimensions on the frequency and Q factor of resonances was studied. Practical recommendations for the choice of sizes of bar that are necessary to provide the desired resonance frequency and bandwidth are given.
Keywords: notch-filters; rectangular waveguides; reflection cell